2011
DOI: 10.2319/081010-473.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of facemask treatment anchored with miniplates after alternate rapid maxillary expansions and constrictions; A pilot study

Abstract: This treatment approach can offer an advantage for correcting mild/moderate maxillary retrusion in Class III patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
4
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 37 publications
7
68
4
2
Order By: Relevance
“…Two studies 8,9 have shown that the facemasks in conjunction with bone-borne anchorage devices result in greater maxillary advancement than those with tooth-borne anchorage devices, but this was not found in our study. The probable reason might have been due to magnitude of protraction force.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Two studies 8,9 have shown that the facemasks in conjunction with bone-borne anchorage devices result in greater maxillary advancement than those with tooth-borne anchorage devices, but this was not found in our study. The probable reason might have been due to magnitude of protraction force.…”
Section: Discussioncontrasting
confidence: 56%
“…In patients treated with facemask and various bone-borne anchors, maxillary advancement ranged from 2.0 mm to 4.8 mm. [4][5][6][7][8][9] Singer et al 4 reported maxillary advancement of 4 mm by using osseointegrated implants as an adjunct to facemask therapy. Enacar et al 5 demonstrated that the entire maxillary complex was affected positively by 4 mm of advancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12-25 TAD-anchored MP with miniplates is most frequently used; this procedure uses extraoral elastics [12][13][14][15][16][17][18][19][20] and intermaxillary elastics. [21][22][23][24][25] In the former type, the miniplates are placed on the infrazygomatic crest or the lateral nasal walls of the maxilla, thus abandoning the intraoral appliance.…”
Section: Introductionmentioning
confidence: 99%
“…In tegenstelling tot de eerder genoemde tandgedragen methode werden hierdoor geen dentoalveolaire effecten in de maxilla waargenomen (Kaya et al, 2011). Behandelingen met een omgekeerde headgear zijn echter afhankelijk van de medewerking van de patiënt.…”
Section: Behandeling Met Behulp Van Skelettale Verankeringunclassified